2018
DOI: 10.1002/2017jg004173
|View full text |Cite
|
Sign up to set email alerts
|

Functional Group, Biomass, and Climate Change Effects on Ecological Drought in Semiarid Grasslands

Abstract: Water relations in plant communities are influenced both by contrasting functional groups (grasses and shrubs) and by climate change via complex effects on interception, uptake, and transpiration. We modeled the effects of functional group replacement and biomass increase, both of which can be outcomes of invasion and vegetation management, and climate change on ecological drought (soil water potential below which photosynthesis stops) in 340 semiarid grassland sites over 30 year periods. Relative to control v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 92 publications
(143 reference statements)
0
13
0
1
Order By: Relevance
“…Sustainable management of dryland ecosystems faces many challenges such as overgrazing, urban development, wildfire, invasive species introduction, and other anthropogenic disturbances (Schwinning et al 2008). Land managers seeking to recover plant and ecosystem properties following these disturbances must also overcome drought, extreme temperature fluctuations, and limited resources when undertaking restoration projects (e.g., Bainbridge 2012, Kildisheva et al 2016, Wilson et al 2018). Guidelines for restoration‐relevant research and land management actions have emerged internationally to ensure the right seed is sown in the right place at the right time to improve restoration outcomes (Hawke 1989, Oldfield and Olwell 2015, Mcdonald et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable management of dryland ecosystems faces many challenges such as overgrazing, urban development, wildfire, invasive species introduction, and other anthropogenic disturbances (Schwinning et al 2008). Land managers seeking to recover plant and ecosystem properties following these disturbances must also overcome drought, extreme temperature fluctuations, and limited resources when undertaking restoration projects (e.g., Bainbridge 2012, Kildisheva et al 2016, Wilson et al 2018). Guidelines for restoration‐relevant research and land management actions have emerged internationally to ensure the right seed is sown in the right place at the right time to improve restoration outcomes (Hawke 1989, Oldfield and Olwell 2015, Mcdonald et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…FGs are differentiated by their characteristics and corresponding relationships with various environmental factors as previously described. Wilson, et al [31] concluded that phenology, biomass allocation, plant height, interception, and rooting depth caused different FGs to have differing impacts on evaporation, soil water availability, and drought conditions. The same concept is true for FGs and corresponding CS rates and Reich, et al [14] confirms that differences in leaf area ratio, photosynthetic rate, and other characteristics between C3 grasses, C4 grasses, forbs, and legumes which resulted in differences in CS rate for these different FGs.…”
Section: Considerations For Functional Groups In Carbon Sequestrationmentioning
confidence: 99%
“…The severity of the recent synoptic California drought and its effects on vegetation were most notably documented through upland forest canopy water stress and mortality (Asner et al, 2016;Fettig et al, 2019;Goulden & Bales, 2019), as well as through declining groundwater levels that heavily impacted agricultural production throughout the Central Valley (Thomas et al, 2017;Xiao et al, 2017). Similarly, the intensified moisture loss and accelerated ET also impacted lowland vegetation in Southern California, including differential species responses within chaparral and grassland ecosystems (Breshears et al, 2005;Gremer et al, 2015;Okin et al, 2018;Wilson et al, 2018). While the landscape in Southern California is dominated by vast stretches of brown grasslands during the dry season, the 2012-2019 drought in Santa Barbara Country was so intense and prolonged compared to the rest of the state (Figure 2), that it propagated into multiple years of soil moisture deficits, early die-off of grasses (Figures 4-6), and an overall drier landscape primed for fire.…”
Section: Discussionmentioning
confidence: 99%